Retpoline technique for mitigating spectre attack - Mohd Fadzil, Abdul Kadir; Ahmad Faisal Amri, Abidin @ Bharun; Fauziah, Ab. Wahab; Mohamad Afendee, Mohamed; Wong, Jinkee (2019)
The Speculative execution (Spectre) is a chip attempting to predict the future to improve the system performance which involves multiple logical branches. It will start working out the math for all those branches before the program even has to decide between them. Normally, it works together with caching which is to speed up the memory access by filled with the data that will need some and often the output of the speculative execution is stored here. The speculative execution and caching in the operating system improve the overall system and operating system performance through the prediction of data or resources to be used and cache memory for quick access to data or resources. The problem arises where this function could allow potential attackers to get access to data they should not have access to by exploiting Spectre attack which also known as side-channel attack and Meltdown. Spectre attack and Meltdown open up the possibilities for dangerous attacks which involved the breach of security and confidentiality of the user. Various techniques and patches have been introduced to mitigating the Spectre attack and Meltdown. In this project, we study the technique used to mitigate the Spectre attack variant 2 introduced by Google called Retpoline technique in the networking virtualised environment.